Adult Talk During Book Reading for Preschoolers With ASD: Links With Literacy Outcomes. (June 2023) - Gasamis, Colin; Sanders, Elizabeth; Hudson, Roxanne F.; Chiou, Michelle
Calls for interventions in early childhood that best prepare children with autism spectrum disorder (ASD) to have inclusive school experiences have been numerous. Although there is a developing literature on the efficacy of interactive book reading (IBR) for this population, it is still unclear which aspects of IBR benefit these children and in what way. To address this gap, we reanalyzed data from a recently completed experiment comparing IBR with other early literacy instruction for preschoolers with ASD. Our results showed that frequency of tutors' use of completion prompts used during IBR was uniquely predictive of better gains in phonological awareness. In addition, tutors' frequency using open-ended prompts was associated with increased gains in print knowledge. Furthermore, both findings held true after controlling for language gains. Results have implications for the types of structure and support that adults might provide young children with ASD during IBR.